2016
DOI: 10.1002/14651858.cd011958.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral Astragalus (Huang qi) for preventing frequent episodes of acute respiratory tract infection in children

Abstract: We found insufficient evidence to enable assessment of the effectiveness and safety of oral Astragalus as a sole intervention to prevent frequent ARTIs in children aged up to 14 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Notably, YPFG contains astragalus (AR, Huangqi), the main active components of which are polysaccharides, saponins, and flavonoids, which can promote the maturation of acquired immune cells, enhance antibodies and improve innate immune function ( 56 ). Studies have confirmed astragalus, combined with other herbal treatments, can reduce the risk of acute respiratory infection (ARTIS) in children ( 57 ). The mechanism of YPFG regulating immune function is related to bile acid and glycerol phospholipid metabolism, and the active components of YPFG can affect this metabolism and inhibit inflammation ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, YPFG contains astragalus (AR, Huangqi), the main active components of which are polysaccharides, saponins, and flavonoids, which can promote the maturation of acquired immune cells, enhance antibodies and improve innate immune function ( 56 ). Studies have confirmed astragalus, combined with other herbal treatments, can reduce the risk of acute respiratory infection (ARTIS) in children ( 57 ). The mechanism of YPFG regulating immune function is related to bile acid and glycerol phospholipid metabolism, and the active components of YPFG can affect this metabolism and inhibit inflammation ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese medicine practice over thousands of years has confirmed that A. membranaceus functions to replenish qi, which strengthens body resistance, promotes diuretic detoxification, heals sores, and prompts muscles. 9 12 It contains many chemical components, such as polysaccharides, saponins, flavonoids, amino acids, and certain trace elements. Our study found that Chahuangjing exhibits diuretic, tritium-removing, and free-radical-scavenging effects, which reduce internal HTO radiation injury.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, another study was conducted to assess the effectiveness and safety of oral AR for preventing frequent episodes of acute respiratory tract infections (ARTIs) in children. The results indicated that the intake of AR alone or in combination with other drugs can effectively enhance the immune function and prevent upper respiratory tract infection in children [171].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%